Succession of the Gut Microbiome in the Tibetan Population of Minjiang River Basin - Li, Jun; Sun, Lin; He, Xianlu; Liu, Jing; Wang, Dan; Han, Yuanping; Chen, Baijun; Li, Xuemei; Song, Lingmeng; Yang, Wen; Zuo, Luo; Sun, Jingping; et al. (Frontiers in Microbiology, 2022)
Tibetans are one of the oldest ethnic groups in China and South Asia. Based on the analysis of 1059 Tibetans in the Minjiang River basin at an altitude of 500-4001 m, we found that the dominant phyla of the Tibetan population were Bacteroidetes and Firmicutes, and the main genera were Prevotella and Bacteroides. We further evaluated 115 total parameters of 7 categories, and results showed that altitude was the most important factor affecting the variation in the microbial community. In the process of migration from high altitudes to the plain, the gut microbial composition of late immigrants was similar to that of plateau aborigines. In addition, migration from low altitude to high altitude, the microbial community was similar to the high-altitude population increased. Changes in these microbials are related to the metabolism, disease incidence and cell functions of the Tibetan population. The results of other two cohorts (AGP and Z208) also showed the impact of altitude on the microbial community. Our study demonstrated that altitude of habitation is an important factor affecting the enterotype of the microflora in the Tibetan population and the study also provided a basis to explore the interaction of impact parameters with gut microbiome for host health and diseases.